Parity and obesity. Issue 3 (September 1981) - Heliövaara, M; Aromaa, A
Abstract : Parity was found to be closely related to adiposity and prevalence of obesity in a population sample of 17 688 non-pregnant women aged 25-84. The women took part in multiphasic screening examinations in various parts of Finland in 1966-72. The relationship between parity and obesity was independent of other factors such as +geographical area, region, marital status, occupation, smoking habits, or incapacity for work. Pregnant women were considered to be an important target population for nutritional education.